Velocity model uncertainty in block cave microseismic monitoring: a case for distributed acoustic sensing - Furlong, J.; Anderson, Z. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
For microseismic monitoring in mines, velocity model error typically accounts for the largest source of uncertainty in microseismic event location, yet it is routinely underestimated. This paper presents a synthetic modelling study comparing the location performance of distributed acoustic sensing (DAS) to conventional geophone arrays under increasing velocity model perturbation. Using a synthetic 3D velocity model representative of an operating block cave, we demonstrate that the spatial density achievable with DAS provides measurable robustness to velocity model error that sparse geophone arrays cannot match. Array bias, 1-component versus 3-component monitoring, limitations of synthetic-only validation, and the distinction between random and structured velocity perturbations are discussed.